2020
DOI: 10.3389/fpubh.2020.601961
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Perspective on Prescribing Patterns and Knowledge on Antimicrobial Use and Resistance in Penang, Malaysia: A Qualitative Study

Abstract: Background: Unnecessary antimicrobial use is an emerging problem throughout the world. To design future interventions to ensure rational antimicrobial use and decrease the risk of antimicrobial resistance, physician's knowledge and prescribing practices of antimicrobials should be assessed. Therefore, the main objective of this study is to investigate the physician's knowledge along with their prescribing patterns of antimicrobials in their health care system.Methods: The present qualitative study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Previous qualitative studies regarding antibacterial drug use during COVID-19 were mostly developed in primary care settings where the clinical scenario along with the disease severity were completely different; therefore, we could not compare our findings regarding the complex rationale behind antibiotic prescription. However, a previous qualitative study published before the emergence of COVID-19 showed that physicians were likely to base their decisions to administer antimicrobial drugs based solely on clinical grounds, which were no longer appliable given the fact that the patient–physician interactions were severely shortened due to the risk of SARS-CoV-2 transmission [ 20 ]; this idea was also presented by Borek et al in a qualitative study which involved general practitioners from England [ 21 ]. Regarding the presence of lung consolidation, in the Estrada et al study [ 14 ], not only alveolar infiltrates but also interstitial infiltrates were linked to antibiotic prescriptions, while the presence of bilateral interstitial infiltrates were strongly associated with what was considered inappropriate antibiotic use in the study of Calderón-Parra et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative studies regarding antibacterial drug use during COVID-19 were mostly developed in primary care settings where the clinical scenario along with the disease severity were completely different; therefore, we could not compare our findings regarding the complex rationale behind antibiotic prescription. However, a previous qualitative study published before the emergence of COVID-19 showed that physicians were likely to base their decisions to administer antimicrobial drugs based solely on clinical grounds, which were no longer appliable given the fact that the patient–physician interactions were severely shortened due to the risk of SARS-CoV-2 transmission [ 20 ]; this idea was also presented by Borek et al in a qualitative study which involved general practitioners from England [ 21 ]. Regarding the presence of lung consolidation, in the Estrada et al study [ 14 ], not only alveolar infiltrates but also interstitial infiltrates were linked to antibiotic prescriptions, while the presence of bilateral interstitial infiltrates were strongly associated with what was considered inappropriate antibiotic use in the study of Calderón-Parra et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A semistructured, in-depth interview guide was developed based on a comprehensive literature review (Röing et al, 2020 ; Akhtar et al, 2020 ; Saleh et al, 2021 ; Liu et al, 2020 ; Influenza Vaccination and Antimicrobial Resistance: Strategic Recommendations, 2021 ; Tosepu et al, 2021 ). Three experts in the field reviewed and validated the interview guide.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding healthcare commissioners’ perceptions of AR during the pandemic in Saudi Arabia and other countries, previous studies have explored the perceptions of the public, pharmacists, nurses, and other HCWs regarding antibiotic use and resistance (Karuniawati et al, 2020 ; Akhtar et al, 2020 ; Saleh et al, 2021 ). Moreover, HCWs in the KSA were evaluated with regard to their knowledge, attitudes, and practices regarding AR during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a structured, standardized, and self-administered questionnaire following an extensive literature review [ 34 , 35 , 36 , 37 ]. The questionnaires were pre-tested among twenty physicians and were refined based on their inputs ( Supplementary File S1 ).…”
Section: Methodsmentioning
confidence: 99%